Getting miRNA Therapeutics into the Target Cells for Neurodegenerative Diseases: A Mini-Review - Wen, Ming Ming (Frontiers in Molecular Neuroscience, 2016)
Abstract: MiRNAs play important roles in modulating gene expression in varying cellular processes and disease pathogenesis, including neurodegenerative diseases. Several miRNAs are expressed in the brain and control brain development and identified as important biomarkers in the pathogenesis of motor- and neuro-cognitive diseases such as Alzheimer, Huntington's and Parkinson's diseases and amyotrophic lateral sclerosis. These remarkable miRNAs could be used as diagnostic markers and therapeutic targeting potential for many stressful and untreatable progressive neurodegenerative diseases. To modulate these miRNA activities, there are currently two strategies involved; first one is to therapeutically restore the suppressed miRNA level by miRNA mimics (agonist), and the other one is to inhibit miRNA function by using antimiR (antagonist) to repress overactive miRNA function. However, RNAi-based therapeutics often faces in vivo instability because naked nucleic acids are subject to enzyme degradation before reaching the target sites. Therefore, an effective, safe and stable bio-responsive delivery system is necessary to protect the nucleic acids from serum degradation and assist their entrance to the cells. Since neuronal cells are non-regenerating, to design engineered miRNAs to be delivered to the CNS for long term gene expression and knockdown is representing an enormous challenge for scientists. This article provides an insight summary on some of the innovative strategies employed to deliver miRNA into target cells. These viral and non-viral carrier systems hold promise in RNA therapy delivery for neurodegenerative diseases.